Osmotina de Plumeria rubra: identificação, clonagem molecular, modelamento tridimensional e possível efeito mimético da adiponectina - Nishi, Beatriz Caroline (2016)
Pathogenesis-related proteins (PRs) are expressed in response to pathogenic infections and abiotic stresses. PR-5 family includes proteins related to thaumatin and osmotin. In this study, the presence of an ~22 kDa osmotin-like protein in Plumeria rubra latex was confirmed by western blot assay using anti-CpOsm antibodies, as described by Freitas et al., 2015. The cDNA fragment encoding this osmotin (PrOsm) was cloned, and then the predicted protein was characterized and modeled in silico. The amplification of the cDNA fragment encoding the PrOsm was carried out by RTPCR. The PCR product was ligated into pGEM-T Easy vector and cloned in E. coli DH5α cells. Clones obtained were submitted to sequencing. The computational analysis of the deduced sequences of P. rubra osmotins (PrOsms) showed that the proteins have an apparent molecular weight about 22 kDa and contain 16 cysteine residues involved in 8 disulfide bonds, stabilizing the protein structure. The PrOsms structure exhibits a typical architecture of TLPs, composed by three domains. Mapping of the electrostatic potentials showed that PrOsms contain, on its surface, an acidic cleft, between domains I and II. The PrOsms were evaluated for their ability to interact with human adiponectin receptors (AdipoR1 and AdipoR2) in silico. Molecular docking suggests that PrOsms are able to interact with adiponectin receptors, similarly to AdipoQ, being potential therapeutic targets for the control of obesity-related diseases, including type 2 diabetes and metabolic syndrome.